2017
DOI: 10.5032/jae.2017.03219
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Impacts of a Faculty Development Program for the Internationalization of Curriculum in Higher Education

Abstract: Faculty development programs for internationalization of the curriculum in higher education are often evaluated for short- and medium-term outcomes, but more long-term assessments are needed to determine impact. This study examined the long-term (6 years) impacts on faculty from colleges of agriculture after participating in a one-year professional development program for internationalization, which included a two-week experience in Costa Rica with immersion in both pedagogical and global topics. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Internationalization is often associated with the mobility of students, teachers, and other HEI staff [4]. Internationalization of the curriculum in higher education is of growing relevance [4,[19][20][21]. This standardization of higher education is intended both to facilitate a higher flux of students and to consolidate the process of HEIs' internationalization.…”
Section: Internationalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Internationalization is often associated with the mobility of students, teachers, and other HEI staff [4]. Internationalization of the curriculum in higher education is of growing relevance [4,[19][20][21]. This standardization of higher education is intended both to facilitate a higher flux of students and to consolidate the process of HEIs' internationalization.…”
Section: Internationalizationmentioning
confidence: 99%
“…This entails the emergence of a new teaching-learning model, which requires that its actors "keep pace with the fast update of information transforming it into knowledge through experience and critical thinking. As such, the role of formal education nowadays is more related to teaching how to learn rather than teaching what to learn" [22] (p. 19).…”
Section: Internationalizationmentioning
confidence: 99%
“…In fact, engaging with colleagues in a professional development program has been shown to be a significant factor in the long-term effectiveness of such programs. Urban, Navarro, and Borron (2017) in their qualitative study of a faculty development program for the internationalization of higher education curricula reported that strengthened peer relationships were a common and major outcome that contributed to interdepartmental collaborations on both professional and personal levels. Furthermore, Leask (2013) emphasized that the process of internationalization of the curriculum is a form of participatory research that is a dynamic and collaborative process ultimately aimed at the improvement of student learning.…”
Section: Discussionmentioning
confidence: 99%
“…One critical challenge lies in creating for faculty effective professional development opportunities that emphasize pedagogical and curricular change which embraces linguistically and socioculturally diverse experiences. While there has been considerable discussion about the role of faculty in internationalization, often as a driving force, there are few studies that examine faculty professional development programs and their effectiveness, especially in the long term (Urban, Navarro, & Borron, 2017).…”
mentioning
confidence: 99%
“…Other researchers (Niehaus & Williams, 2016; Urban et al, 2017) offered analyses of faculty’s experiences participating in various training programs for internationalization of their courses. Niehaus and Williams (2016) studied a 4-year global faculty development program aimed at transforming faculty perspectives and internationalizing the curriculum.…”
Section: Literature Reviewmentioning
confidence: 99%